(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this paper, we establish a modified Laplace decomposition method for nonlinear volterra integral and integro-differential equations. This technique differs from the general Laplace decomposition method because of the terms involved in Adomian polynomial.We have used Newton Raphson formula in place of the u_i in Adomian polynomial. The proposed scheme is investigated with some illustrative examples and has given reliable results.